2001
DOI: 10.2355/isijinternational.41.389
|View full text |Cite
|
Sign up to set email alerts
|

Natural Gas Decompression Behavior in High Pressure Pipelines.

Abstract: This paper gives the analysis in the natural gas decompression behavior in pipelines as one of the important items for predicting the fracture safety of latest high-pressure natural gas transmission. By combining "British Gas Theoretical Model of Rich Gas Decompression" and "BWRS Equation of State", authors successfully developed the computational program, which can calculate dual-phase decompression curves of the natural gases. In the calculated results, the phenomenon of the "plateau" in the dual-phase decom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Detailed method can be found in another paper in this volume, 10) and here only the calculated results will be shown. The comparison between the calculated decompression curve of the "Typical Natural Gas" and the calculated decompression curve of the "Nitrogen Gas" is shown in Fig.…”
Section: The Effect Of the Difference In Gasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed method can be found in another paper in this volume, 10) and here only the calculated results will be shown. The comparison between the calculated decompression curve of the "Typical Natural Gas" and the calculated decompression curve of the "Nitrogen Gas" is shown in Fig.…”
Section: The Effect Of the Difference In Gasesmentioning
confidence: 99%
“…From the analyzed result of the full-scale burst tests, HLP Committee adopts the diameter of the pipe "D" equal to the assumptive initial half crack length "l 0 " for the crack propagating simulation. This assumptive initial crack length represents "the assumptive non-decompression distance" caused from the fracture initiation process, during which the inner gas can't escape effectively because of the narrow opening of the crack and the assumption of the "full-bore opening" 10) does not hold. Therefore, this assumptive initial crack length apparently affected by the degree of the crack opening during the fracture initiation process, so it seems to be affected mainly by the failure pressure level.…”
Section: The Effect Of the Gas Ratiomentioning
confidence: 99%
“…One such important factor which is receiving increasing attention 5,6 is the presence of impurities. [11][12][13][14] Based on shock tube experiments using diff erent surface roughness pipes, Botros et al 15 for example have recently shown that in the case of pressurized hydrocarbons, ignoring pipe friction may result in overestimating the decompression wave speed, with the eff ect becoming more signifi cant with increasing line pressure and reducing pipe diameter. 7,8 Th e impact of the latter on the decompression behavior of the CO 2 stream and the appropriate pipeline fracture toughness has been the subject of a number of studies.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However such studies ignore the impact of pipe wall heat transfer and friction on the fl uid decompression behavior. [11][12][13][14] Based on shock tube experiments using diff erent surface roughness pipes, Botros et al 15 for example have recently shown that in the case of pressurized hydrocarbons, ignoring pipe friction may result in overestimating the decompression wave speed, with the eff ect becoming more signifi cant with increasing line pressure and reducing pipe diameter. Th is is important since over-predicting the decompression wave speed results in underestimating the pipe toughness required to arrest a fracture.…”
Section: Introductionmentioning
confidence: 99%
“…All properties are calculated using the Peng-Robinson EOS in DECAY. The approach taken in the model developed by Makino et al [16] is similar to the model of Jones and Gough, but it uses the BWRS EOS.…”
Section: Introductionmentioning
confidence: 99%